Implementasi Post-Boot Package Installation pada OpenStack untuk Image berbasis Linux - Bobby Kwariawan; Henry Novianus Palit; Agustinus Noertjahyana (Jurnal Infra, 2019)
Cloud Computing technology is currently growing rapidly, so there have been a lot of companies plunged into using Cloud Computing Technology with the IaaS model (Infrastructure as a Service). OpenStack is one of the Cloud frameworks that is often used for Private Cloud Implementation. However, often Cloud users make configurable Virtual Machine Image as needed for different servers as templates to be easily deployed in the future. This can lead to waste of storage.Implementation of Package Installation Automation can reduce storage waste, by storing only 1 Virtual Machine Image then installing Package automatically using user-data features on cloud-init as needed, so Cloud users no longer need to manually install packages then save the Image results that were carried out by the package installation.Test results on OpenStack with Single-Node deployment show that this implementation can produce storage efficiency with an average of 79 % for Red Hat Enterprise Linux Image and 81 % for Ubuntu Image. But there are also inefficiencies in time with an average of 83 % for Red Hat Enterprise Linux and 71 % for Ubuntu Image.